The River Potential in the Sumber Marga Telang District as a Rowing Sport Center - Widya Handayani (International Conference on Science, Education, and Technology, 2021)
This study aims to determine the potential of the river in Sumber Marga Telang District as a center for rowing sport and to determine the community's response to the rowing sport. This research was a type of qualitative research with data collection techniques using interviews, observation and documentation. From the results of the research, it was found that Sport officials and the village community were interested in rowing sport on the Sumber Marga Telang River which would increase the economic value, but were still constrained by the support of the Regional Government and the Central Government.